Systematic analysis of the form factors of Bc → ηc, J/ψ and corresponding weak decays - Bin Wu; Guo-Liang Yu; Jie Lu; Zhi-Gang Wang (Physics Letters B)
The form factors of Bc→ηc and Bc→J/ψ are analyzed in the framework of three-point QCD sum rules. In the calculations, the contributions of the vacuum condensate terms 〈gs2GG〉 and 〈gs3GGGf〉 are considered. In addition, the decay widths and branching ratios of several decay channels are predicted by using the calculated form factors. These decay processes include the nonleptonic decays Bc−→ηcπ−, ηcK−, ηcρ−, ηcK⁎−, J/ψπ−, J/ψK−, J/ψρ−, J/ψK⁎−, and the semileptonic decays Bc−→ηclν¯, J/ψlν¯. These results about the form factors and decay properties of Bc meson provide useful information for us to study the heavy-quark dynamics and find new physics beyond Standard Model.